Prevalence and related factors of psychological distress among cancer inpatients using routine Distress Thermometer and Chinese Health Questionnaire screening - Chiou YJ (Dove Medical Press, 2016)
Yu-Jie Chiou,1 Nien-Mu Chiu,1 Liang-Jen Wang,2 Shau-Hsuan Li,3 Chun-Yi Lee,1 Ming-Kung Wu,1 Chien-Chih Chen,1 Yi-Shan Wu,1 Yu Lee1 1Department of Psychiatry, 2Department of Child and Adolescent Psychiatry, 3Department of Hematology-Oncology, Kaohsiung Chang Gung Memorial Hospital, Chang Gung University College of Medicine, Kaohsiung, Taiwan, Republic of China Background: Clinical practice guidelines suggest routine screening for distress among cancer patients for immediate early psychiatric care. However, previous studies focusing on routine screening for psychological distress among cancer inpatients in Taiwan are scant. Thus, the aim of this study was to evaluate the prevalence and related factors of psychological distress and mental illness among cancer inpatients in Taiwan. Patients and methods: This study was conducted as a retrospective chart review in a general hospital in southern Taiwan. Cancer inpatients were regularly screened by nursing staff using the Distress Thermometer and the 12-item Chinese Health Questionnaire. Positive screening results on either instrument were followed by a non-commanded referral to psychiatrists for clinical psychiatric diagnosis and treatment. Results: Of the 810 participants in this study, 179 (22.1%) were recognized as having psychological distress. Younger age (odds ratio [OR] =1.82), having head and neck cancer (OR =2.43), and having not received chemotherapy (OR =1.58) were significantly related to psychological distress. Among the 56 patients (31.3%) with psychological distress who were referred to psychiatrists, the most common mental illness was adjustment disorder (n=22, 39.2%), followed by major depressive disorder (n=13, 23.2%), depressive disorder not otherwise specified (n=6, 10.7%), and anxiety disorder not otherwise specified (n=4, 7.1%). Conclusion: Our study indicated that cancer inpatients with psychological distress were more likely to be younger in age, have head and neck cancer, and have not received chemotherapy. The most common psychiatric disorder was adjustment disorder. Early detection of psychological distress and prompt psychiatric consultation and management are very important for cancer inpatients. Keywords: psychological distress, cancer inpatients, prevalence, related factors, Distress Thermometer, Chinese Health Questionnaire